Dental caries prevalence among Type 1 diabetes mellitus (T1DM) 6- to 12-year-old children in Riyadh, Kingdom of Saudi Arabia compared to non-diabetic children - Abid Hamoud Al-Badr; Albandary Hassan AlJameel; Hassan Suliman Halawany; Yousra Hussein Al-Jazairy; Mohamad Khalid Alhadlaq; Nassr Saleh Al-Maflehi; Jehan Adnan Al-Sharif; Vimal Jacob; Nimmi Abraham (Elsevier, 2021)
Objective: The aim of this study was to compare the prevalence of dental caries among groups of 6-12-year-old children with and without Type 1 diabetes mellitus (T1DM) in Riyadh, Saudi Arabia, taking into account oral health behaviour, diet, and salivary parameters. Methods: The study was designed as a comparable study of dental caries experience between T1DM and non-diabetic groups of children. The total sample size of 209 participants consisted of 69 diabetic and 140 non-diabetic children. Oral hygiene, diet and socio-economic status were collected using a pre-tested questionnaire. Caries was recorded in terms of decayed and filled permanent and primary teeth (DFT/dft). Salivary microbial counts and pH levels were recorded using Caries Risk Test (CRT) kit. Student's t-test, the chi-squared test, linear regression and one-way analysis of variance were performed P-value of 0.05 considered significant. Results: The mean dft scores for the diabetic and non-diabetic groups were 3.32 ± 0.78 and 3.28 ± 0.71 (mean ± SD), respectively (p = 0.458). The mean DFT scores for the diabetic and non-diabetic groups were 1.62 ± 0.65 and 1.96 ± 0.65, respectively (p = 0.681). Diabetic children visited dentists more often than non-diabetic children did (p = 0.04), and had lower consumption of both sweets (p = 0.003) and flavoured milk (p = 0.002) than the non-diabetic group. Furthermore, analysis showed that the diabetic children had medium oral pH levels (pH = 4.5-5.5), whereas the non-diabetic children tended to have high (pH ≥ 6.0) oral pH; this difference was statistically significant (p = 0.01). In addition, the diabetic group had higher Lactobacillus levels than the non-diabetic group (p = 0.04). Conclusion: The difference in caries prevalence between the diabetic and non-diabetic children was not statistically significant. The CRT analysis revealed a higher frequency of "critical" pH values (pH = 4.5-5.5) and higher Lactobacillus counts in diabetic children than in non-diabetic children, which indicated a higher caries risk in the former group.